Optimizing a Biobjective Production-Distribution Planning Problem Using a GRASP - Martha-Selene Casas-Ramírez; José-Fernando Camacho-Vallejo; Rosa G. González-Ramírez; José-Antonio Marmolejo-Saucedo; José-Manuel Velarde-Cantú (Complexity)
This paper addresses a biobjective production-distribution planning problem. The problem is formulated as a mixed integer programming problem with two objectives. The objectives are to minimize the total costs and to balance the total workload of the supply chain, which consist of plants and depots, considering that it represents a company vertically integrated. In order to solve the model, we propose an adapted biobjective GRASP to obtain an approximation of the Pareto front. To evaluate the performance of the proposed algorithm, numerical experimentations are conducted over a set of instances used for similar problems. Results indicate that the proposed GRASP obtains a relatively small number of nondominated solutions for each tested instance in very short computational time. The approximated Pareto fronts are discontinuous and nonconvex. Moreover, the solutions clearly show the compromise between both objective functions.